A finite–element model for simulation of carbon dioxide sequestration. Issue 3 (1st November 2013) - Fang, Yilin; Bao, Jie; Xu, Zhijie
Abstract : The authors present a hydro-mechanical model, followed by stress, deformation and shear-slip failure analysis for geological sequestration of carbon dioxide (CO2 ). The model considers the poroelastic effects by taking into account the two-way coupling between the geomechanical response and the fluid flow process. Analytical solutions for pressure and deformation fields were derived for a typical geological sequestration scenario in our previous work. A finite–element approach is introduced here for numerically solving the hydro-mechanical model with arbitrary boundary conditions. The numerical approach was built on an open-source finite–element code (Elmer), and results were compared to the analytical solutions. The shear-slip failure analysis was presented based on the numerical results, where the potential failure zone is identified. Information is relevant to the prediction of the maximum sustainable injection rate or pressure. The effects of caprock permeability on the fluid pressure, deformation, stress and the shear-slip failure zone were also quantitatively studied. It was shown that a larger permeability in caprock and base rock leads to a larger uplift but a smaller shear-slip failure zone.